Game Edukasi Sebagai Media Pembelajaran Perhitungan Dasar Matematika Menggunakan Construct 2 Dengan Metode GDLC - Victor Alwi Hura; Rismayanti; Nur Wulan (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
Educational games are a form of fun learning for children, where educational games can motivate the learning process and involve children so that the learning process is more enjoyable, where games play a role in fulfilling learning objectives, namely so that a child is interested and comfortable when learning. Mathematics is a lesson that discusses numbers, how to calculate and formulas that use logic. This research aims to change conventional learning methods into simulation learning methods with educational game applications and develop children's creativity, because educational games have elements of challenge, accuracy, reasoning power and ethics. In this game, elementary school students can enjoy educational games based on Android to increase their knowledge and learn to count by answering questions in this educational game such as addition, subtraction, multiplication and division. The research method used in this research is the Game Development Life Cycle (GDLC) method, which is a guide used to determine the steps and criteria that need to be considered in building a good quality game. Construct 2 is a 2D game engine for HTML5 developed by Scirra Ltd, a start-up company headquartered in London. This game engine was developed with the concept of behavior and event attachment so that logic in the game can be built without having to type a single line of coding, just drag and drop. The result of this research is the formation of an educational game for basic mathematical calculations using Android-based application media to help elementary school students learn basic mathematical calculations with an educational game.